Effects of matrine on proliferation and apoptosis of cultured retinoblastoma cells - Zhao, Bowen; Jonas, Jost B. (Graefe's archive for clinical and experimental ophthalmology, 2012)
BackgroundExtracted from the traditional Chinese medicine of Kushen, matrine is an alkaloid with potential anti-neoplastic and anti-inflammatory effects. Here, we examined the effect of matrine on proliferation and apoptosis of cultured retinoblastoma cells.MethodsThe retinoblastoma cell lines Y79, WERI-RB1 and SO-RB50 were treated with matrine in increasing concentrations from 0.2-1.1 mg/ml for 24 hours, and the cell proliferation rate was measured. The cells were exposed to matrine at 50% inhibition concentration (IC50) for 12, 24 and 48 hours. Cell cycle was analyzed by flow cytometry, concentration of proteins regulating cell cycle and apoptosis was determined by Western blot, apoptosis rate was measured by TUNEL staining, and cell morphology was assessed by electron transmission microscopy.ResultsThe retinoblastoma cell lines Y79, WERI-RB1 and SO-RB50 showed an increased inhibition of cell proliferation with increasing matrine concentrations. Applying the IC50 concentration of matrine, the alteration of the cell cycle, including a reduced percentage of the S phase, was significantly (P < 0.01) associated with a longer treatment time by matrine. Correspondingly, the cell-cycle-associated proteins P21 and P27 were up-regulated and the protein cyclinD1 was down-regulated. The apoptosis-associated protein Bcl-2 was down-regulated, and Bax was up-regulated. In a similar manner, the apoptosis rate was significantly increased with longer treatment time.ConclusionsMatrine added to cultures of immortalized retinoblastoma cells led to a reduced tumor cell proliferation, decreased rate of mitosis and an increased tumor cell apoptosis, paralleled by corresponding changes in the proteins regulating the cell cycle or apoptosis.